Exploring the pathogenesis of diabetic kidney disease by microarray data analysis - Cao, Haiyan; Rao, Xiaosheng; Jia, Junya; Yan, Tiekun; Li, Dong (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is a major complication of diabetes mellitus, and the leading contributor of end-stage renal disease. Hence, insights into the molecular pathogenesis of DKD are urgently needed. The purpose of this article is to reveal the molecular mechanisms underlying the pathogenesis of DKD. The microarray datasets of GSE30528 and GSE30529 were downloaded from the NCBI Gene Expression Omnibus (GEO) database to identify the common differentially expressed genes (DEGs) between glomerular DKD (GDKD) and tubular DKD (TDKD), respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to analyze the function and pathways of the common DEGs. After constructing the protein-protein interaction (PPI) network and sub-network analysis, three types of analyses were performed, namely identification of hub genes, analysis of the co-expressed network, and exploration of transcription factors (TFs). Totally 348 and 463 DEGs were identified in GDKD and TDKD, respectively. Then, 66 common DEGs (63 up-regulated DEGs and 3 down-regulated DEGs) were obtained in DKD patients. GO and KEGG pathway analyses revealed the importance of inflammation response, immune-related pathways, and extracellular matrix-related pathways, especially chemokines and cytokines, in DKD. Fifteen hub genes from the 66 common DEGs, namely IL10RA, IRF8, LY86, C1QA, C1QB, CD53, CD1C, CTSS, CCR2, CD163, CCL5, CD48, RNASE6, CD52 and CD2 were identified. In summary, through microarray data analysis, the common functions and hub genes greatly contribute to the elucidation of the molecular pathogenesis associated with DKD.